2022
DOI: 10.1002/clt2.12116
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and sensitization variations among asthma and/or rhinitis patients between 2008 and 2018 in China

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…It is well known that HDMs, as the most prevalent aeroallergen, sensitized over 90% of atopic patients in Asia 15 . Compared with a recent national cross‐sectional study conducted from 2008 to 2018, HDMs were still the most popular aeroallergens in China 16 . In our study, HDMs and pollens sensitization was observed in nearly half of the cases of AA patients in the eastern and western regions, respectively, consistent with Lebanese asthmatic patients 17 .…”
Section: Discussionsupporting
confidence: 64%
“…It is well known that HDMs, as the most prevalent aeroallergen, sensitized over 90% of atopic patients in Asia 15 . Compared with a recent national cross‐sectional study conducted from 2008 to 2018, HDMs were still the most popular aeroallergens in China 16 . In our study, HDMs and pollens sensitization was observed in nearly half of the cases of AA patients in the eastern and western regions, respectively, consistent with Lebanese asthmatic patients 17 .…”
Section: Discussionsupporting
confidence: 64%
“…30 In China, national surveys have reported increased allergy prevalence in children between 2008 and 2018 for tree pollens (3% sensitisation to black poplar in 2008 vs 6% in 2018) and dust mite allergens (32% vs 65%). 28 Similar increasing trends were reported in South Korea between 2009 and 2018. 31 The International Study on Asthma and Allergies in Childhood reported a global increasing trend in the prevalence of rhinoconjunctivitis caused by airborne allergens (typically presenting as sneezing or a runny or blocked nose and itchy, watery eyes), between the mid-1990s and early 2000s.…”
Section: Allergies To Airborne Allergenssupporting
confidence: 72%
“…Whereas, globally, dust mite, cockroach, and mould remain a source of major airborne allergens. [24][25][26][27][28] Sensitisation rates and allergy to airborne allergens, including grass pollen, tree pollen, and dust mites, appear to have increased globally in the 21st century. For example, studies conducted in northern Sweden show increased sensitisation rates in children aged 11-12 years in 2010 compared with 2000 (37% positive for allergen-specific IgE in 2010 vs 28% in 2000).…”
Section: Allergies To Airborne Allergensmentioning
confidence: 99%
“…Therefore, a previous study indicated that tIgE developed as a Th2 biomarker involved in regulating the Th2 inflammatory response [ 32 ]. Dust mites are the main allergens in Southern China [ 33 , 34 ], both in airway and skin allergic diseases. Allergen immunotherapy (AIT) is the only treatment for allergic diseases [ 35 ].…”
Section: Discussionmentioning
confidence: 99%